The Effect of Mother Value Training Program to The Social Skill Levels of The 5-6 Years Old Children - Nesliturk, Seviye; Deniz, Mehmet Engin (PEGEM AKAD YAYINCILIK EGITIM DANISMANLIK HIZMETLERI TIC LTD STI, 2014)
This research is planned on the purpose of investigation the effect of Mother Value Training Program (ADEP), which is provided to the mothers of children who attend kindergarten, to the social skills level of 5-6 years old children. In the study, pretest-posttest and experimental research design including the control and experimental groups was used; there were 24 children in each group. The Mother Value Training Program (ADEP) is applied to the mothers of children in the experimental group during 9-weeks. There are 18 sessions and the duration of each is 120 -150 minutes. For the collection of data, Social Skills Improvement System SSIS Parent Form was used. As a result of the analyses, a significant difference was not observed in the control group. However, significantly increasing effect in the social skills related to the communication, cooperation, self-expression, responsibility, empathy, acting together with the group and self-control was observed in the experimental group children. In addition, as a result of the screening test, this effect was also observed in other social skills other than communication.
Keywords: Preschool education; Values education; Social skills; Education & Educational Research